Advanced communications with plastic optical fibers - Heidarialamdarloo, Jamshid (2018)
Nowadays, fiber to the Home/Curb/Building/Cabinet (FTTx) services that interconnect homes with a standard glass optical fiber cables to the core/access optical networks have brought the optical fiber at the doorsteps of our homes. However, the last few miles in home access network is still based on the limited bandwidth electronic component which supports by the cooper wires e.g. Cat-5, 6. The rapid growth of personal smart/mobile electronic devices with new developments such as video on demand, High Definition (HD) and three-Dimension (3D) television (TV), cloud computing, video conferences, etc. has been proposed new challenges for the next generation high bandwidth demand required for subscribers in home access network. In order to meet the more demanding expectations of the end user with new developments, it is necessary to improve the physical infrastructure of the existing in home networks in order to obtain the best ratio between quality of service and price of implementation. Plastic optical fibers (POFs) are point out as a promising transmission medium for short-range communication in compare to the “classic” single/multimode glass optical fibers and current cooper wire technology developments. The main advantages of POF are its easy to install, easy splicing and the possibility of using low cost optical transceivers, capability of being robust, and immunity to electromagnetic noise interference. However, the benefits of large-core POFs come at the expense of a less bandwidth and a higher attenuation than silica-based solution. The main objective of this doctoral dissertation is to explore the possibilities and develop low cost, short reach, high data rate POF-links for in home networks applications. This thesis investigates the use of multilevel modulation in particular, pulse amplitude modulation (PAM in combination of the receiver equalizer in order to overcome the bandwidth limitations of the graded index POFs. The possibility of the using multiple channels over a single fiber to increase the capacity of POF systems using commercially available multimode components is also analyzed in this dissertation. Moreover, a low cost Digitised radio signal over plastic fiber system is proposed and evaluated to deliver digital baseband data for wireline and wireless users in home access network. The deployment will be specified in terms of performance, maximum rates and any degradation that might appear in the network. Furthermore, the possibilities of the microstructured fibers in telecommunication application will be studied with main emphasis on their structural design. The photonic crystal fibers made of different highly nonlinear materials with different structures are optimized to achieve ultra-flat dispersion, high nonlinearity and low confinement loss over a broad range of wavelengths in the perspective of their usage in telecommunication applications.